Investment decision making under uncertainty based on internet recommendations - Šumníková, Alžběta; Borovička, Adam; Daniel, Marek; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The main objective of this bachelor thesis is to make investment portfolios based on recommendations from Internet news servers. Due to high inflation, there is a growing interest in investing even among less involved people, who often follow such suggestions. Firstly, articles are analyzed, and investment instruments are selected. Next, based on the methodology, a statistical overview of historical data is shown, and the simulated values of portfolio returns and risks are generated according to the relevant probability distribution, taking into account regular investment. The resulting parameters are used to optimize a portfolio. The portfolio is composed of disparate investment instruments, such as investment into water, gold, agricultural land, stocks of CEZ company, and stocks of a fond following the S&P 500 index. The results show that online articles provide a helpful overview but not appropriate recommendations. According to news portals and optimization, investing in agricultural land is the most advantageous.
Vedoucí práce: Adam Borovička
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: statistika a ekonometrie [obor bakal. práce]; bakalářské práce; bachelor's theses